CTIM-27. PHASE I/II STUDY OF CONTROLLED IL-12 AS IMMUNOTHERAPY FOR DIFFUSE INTRINSIC PONTINE GLIOMA (DIPG). (9th November 2020) - Goldman, Stewart; Mueller, Sabine; Chi, Susan; Saratsis, Amanda; Allen, Rudy; Buck, Jill; Demars, Nathan; Hadar, Nira; Estupinan, Taylor; Miao, John; Walsh, Erin; Gelb, Arnold; et al.
Abstract: DIPG, which is the leading cause of pediatric brain cancer death with no effective treatment, has neither a highly immunosuppressive nor inflammatory tumor microenvironment (TME). Therefore, eliciting a pro-inflammatory TME may provide therapeutic benefit. We previously demonstrated in adults with recurrent glioblastoma that loco-regional delivery of interleukin 12 administered under the control of the proprietary transcriptional switch RheoSwitch Therapeutic System â (RTS â ) delivered via a replication-incompetent adenovirus ("Controlled IL-12") turned "cold" tumors "hot" for up to 5.8 months (Sci Transl Med. 2019;11(505)) and seemed to improve median overall survival as compared with historical controls (SNO 2020). A multicenter, phase I/II, open-label study (NCT03330197) is determining the safety and tolerability of Ad (2 x 10 11 viral particles) administered by stereotactic intratumoral injection (Day 0) and 14 daily (Days 1 to 14) V doses (10 or 20 mg, body surface area adjusted). The first DIPG subject enrolled was in April 2020 with completion of the first cohort (arm 1, n=3) enrollment anticipated by September 2020. The first subject has tolerated treatment well with no SAEs during the evaluation period. Endogenous serum cytokines increased (including IFN-g 11.4 pg/mL, Day 3), consistent with V crossing the blood-brain barrier and activating the RTS â switch to conditionally produce recombinant IL-12. Other biomarkers include plasma PK and circulating DNA. Follow-up is ongoing and enrollment is proceeding. Since development of effective immunotherapy for DIPG likely depends on eliciting a tumor-specific effector immune response, Controlled IL-12 is a promising immunotherapy candidate. The first DIPG subject shows encouraging data on safety, tolerability, serum cytokines and early signs consistent with a clinical response. After completion of dose-escalation, the study may be expanded up to 30 patients, which will be considered the phase II component of the study.